Pengaruh Milenial Branding Erick Thohir Terhadap Perilaku Pemilih di Pilpres 2019 - Muhamad Afdoli Ramadoni; Rasmillah; Abdur Razzaq (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
The figure of Erick Thohir has emerged into the conversation since he became the chairman of the 2018 ASEAN GAMES committee. Erick Thohir is considered capable of gaining millennial votes in the 2019 presidential election, so Erick Thohir is lined up to be the chairman of the presidential and vice presidential candidate winning team Jokowi - Ma'ruf Amin. According to the millennial classification, Erick Thohir cannot be categorized as a millennial. However, Erick Thohir is considered an influential young figure. The purpose of this study was to determine the views of students of the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang towards Erick Thohir, as well as the influence of Erick Thohir's millennial branding on voting behavior in the 2019 presidential election. The approach in this study was a quantitative approach with correlational methods and the number of samples in this study. opened 46 students of the Da'wah Faculty and the class of 2016 with a simple random sampling technique using a questionnaire and data analysis using SPSS 25. The results of this study are the views of students from the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang towards Erick Thohir are positive and categorized as high, reaching 82.5%. The behavior of choosing students from the Da'wah and Communication Faculty of UIN Raden Fatah Palembang in the 2019 Presidential Election was categorized as tending to reach 69.4%. Meanwhile, Erick Thohir's millennial branding on voting behavior in the 2019 presidential election obtained significance with the results of the t test which showed that it was t_count > t_table or 3,723 > 2,021 with a significant level = 5%. The correlation is relatively low, namely 30.7% between variables X and Y. While the remaining 69.3% is influenced by other factors outside this study.